Innovative Capacity as a Strategic Enabler of Transformational Change in the Public Sector: A Knowledge Management Perspective - Sbongile Nhlapho; Ndwakhulu Tshishonga (European Conference on Knowledge Management, 2026)
This study critically examined the role of innovative capacity in facilitating transformational change within the public sector. It argued that innovation is often overemphasised as a universal solution to governance challenges, yet its effectiveness is contingent upon deeper institutional, organisational and political conditions. Drawing on a qualitative scoping review of literature on public sector innovation, governance and institutional capability, the study synthesised key debates on the drivers, constraints and outcomes of innovation in contemporary public administration. The analysis was grounded in Public Value Theory, the Resource-Based View and New Public Governance, which collectively highlight the interplay between internal organisational capabilities and external governance environments. The findings indicate that innovative capacity is best understood as an embedded and dynamic institutional capability rather than a discrete reform instrument. Whilst leadership, digital transformation, organisational learning and collaborative governance are widely identified as enabling factors, their effectiveness is mediated by bureaucratic structures, regulatory frameworks, political continuity and institutional co-ordination capacity. In many contexts, particularly within developing country public sectors, these constraints limit innovation to incremental adjustments rather than systemic transformation. Digitalisation, whilst an important enabler, often results in “digitised bureaucracy” when not accompanied by organisational reform. The study proposes an Institutional Innovative Capacity Framework (IICF), conceptualising innovation as a multi-level governance system linking enabling capabilities, institutional mediators and public value outcomes. It concludes that sustainable innovation requires integrated institutional reform rather than isolated technological or managerial interventions. The study contributes a more critical and context-sensitive understanding of public sector innovation, emphasising that transformational change depends on the alignment between capability, governance structures and institutional conditions. It also highlights the importance of strengthening state capacity; improving co-ordination mechanisms; and fostering long-term organisational learning to ensure that innovation translates into sustained and meaningful public value outcomes.